Strategi Dayah Perbatasan Safinatussalamah Terhadap Isu Pendangkalan Aqidah di Kecamatan Danau Paris - Abi Hasan; Sarkawi, Sarkawi (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
Abstract Weak knowledge about religion can lead to something fatal, especially in diverse areas, which causes people to sometimes not be able to distinguish between religion and culture, between belief and society, including the Lake Paris sub-district which is a border area with North Sumatra, and is the gateway to The influx of migrants from outside the region, the issue of the shallowing of faith was a flashlight for the Acehnese community, so this needs to be the attention of all parties. To anticipate the occurrence of this silting of faith, several policies were launched by the Aceh government, including the birth of Aceh Qanun No. 8 of 2015 including the basis for consideration of this, as well as the establishment of Dayah in the Aceh border region, including in Aceh Singkil, to be precise, which is located in Danau Paris District its purpose includes fortifying the people from the shallowing of the creed. The strategy carried out by the Safinatussalamah Frontier Dayah on the issue of the shallowing of the creed is through improving the quality of dayah education, in the context of cadre of Da’I as the successor of the missionary struggle, as well as socio-religious activities for the community with the aim of providing religious understanding through Friday sermons and also provide motivation in terms of education through the provision of scholarships for the people of the Danau Paris sub-district, so that it can produce human resources who are knowledgeable and reliable in providing religious understanding for the people of the Danau paris sub-district in the future. Keywords: Strategy, Dayah, Silence of Faith Abstrak Lemahnya pengetahuan tentang agama dapat mengakibatkan sesuatu yang fatal apalagi pada daerah-daerah yang majmuk, yang menyebabkan masyarakat terkadang tidak mampu membedakan antara agama dan budaya, antara keyakinan dan sosial, termasuk kecamatan Danau Paris yang merupakan daerah perbatasan dengan sumatera utara, dan merupakan pintu masuknya pendatang dari luar daerah, Isu pendangkalan akidah ini sempat senter bagi kalangan masyarakat Aceh, sehingga hal ini perlu menjadi perhatian semua pihak. Untuk mengantisifasi terjadinya pendangkalan akidah ini, beberapa kebijakan sempat diluncurkan pemerintah aceh, termasuk lahirnya Qanun Aceh No 8 tahun 2015 termasuk dasar pertimbangan hal tersebut, begitu juga pendirian Dayah diwilayah perbatasan Aceh, termasuk di Aceh Singkil, tepatnya yang berada di Kecamatan Danau paris salah satu tujuannya termasuk membentengi umat dari pendangkalan Akidah. Strategi yang dilakukan Dayah Perbatasan safinatussalamah terhadap Isu pendangkalan Akidah ini, melalui peningkatan mutu pendidikan dayah, dalam rangka pengkaderan Da’I sebagai penerus perjuangan dakwah, begitu juga dengan kegiatan sosial keagamaan bagi masyarakat dengan tujuan untuk memberikan pemahaman agama melalui khutbah jum’at dan juga memberikan motivasi dalam hal pendidikan melalui pemberian beasiswa bagi masyarakat kecamatan Danau Paris, sehingga dapat melahirkan Sumber Daya Manusia yang berilmu dan handal dalam memberikan pemahaman keagamaan bagi masyarakat Kecamatan Danau paris pada masa akan datang. Kata Kunci : Strategi, Dayah, Pendangkalan Akidah